2018
DOI: 10.4194/1303-2712-v18_11_01
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study, the effects of oral administration of an alcoholic and aqueous extract of propolis on growth performance indices, hematological parameters and immune responses of Cyprinus carpio were investigated. Six hundred and thirty juvenile Cyprinus carpio (weighing 58.5 ±4.2 g, Mean±SD) were randomly divided into seven equal groups in triplicates. Three groups (G1 to G3) were fed diets containing 0.1%, 0.25% and 0.5% of Propolis-ethanolic Extract (PEE) respectively, whereas groups 4 to 6 were fed a diet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition, many researchers have studied. Alishahi et al showed that supplementation of food with 0.5% propolis-ethanolic extract could stimulate some innate immune responses and resistance against A. hydrophila infection (Alishahi, Dezfuly, & Mesbah, 2018). The similar results were also found in rainbow trout (Deng et al, 2011), Chinese sucker (Myxocyprinus asiaticus) (Zhang, Gong, Yu, & Yuan, 2009), gilthead seabream (Soltani et al, 2017) and Nile tilapia (Tilapia nilotica) (Santos et al, 2019), indicating propolis extracts have the ability to enhance the non-specific immune response and disease resistance of aquatic animals.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, many researchers have studied. Alishahi et al showed that supplementation of food with 0.5% propolis-ethanolic extract could stimulate some innate immune responses and resistance against A. hydrophila infection (Alishahi, Dezfuly, & Mesbah, 2018). The similar results were also found in rainbow trout (Deng et al, 2011), Chinese sucker (Myxocyprinus asiaticus) (Zhang, Gong, Yu, & Yuan, 2009), gilthead seabream (Soltani et al, 2017) and Nile tilapia (Tilapia nilotica) (Santos et al, 2019), indicating propolis extracts have the ability to enhance the non-specific immune response and disease resistance of aquatic animals.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, a Spirulina ‐supplemented diet in tilapia increased relative percent survival (80%) against A. hydrophila (Watanuki et al 2006). Supplementing the diet with propolis‐ethanolic extract reduced Common Carp Cyprinus carpio mortality from A. hydrophila challenge (Alishahi et al 2018). Additionally, Nile Tilapia fed a Spirulina ‐supplemented diet were protected against A. hydrophila challenge, with a relative percentage survival up to 80% (Ragap et al 2012) and lowered mortality rates against Pseudomonas fluorescens (Ibrahem et al 2013).…”
Section: Discussionmentioning
confidence: 99%